Studies on the Activities of Jonas Pašakauskis SJ (Joannes Poszakowski, 1684–1757) and the First Account of His Life (compendium vitae) - Čiurinskas, Mintautas (Senoji Lietuvos literatūra, 2024)
The main aims of the article are the following: (1) to give a brief reminder of the facts of the life and work of Jonas Pašakauskis (Poszakowski) SJ of the Province of Lithuania (2) to briefly review Lithuanian and foreign research on this highly prolific mid-eighteenth-century writer, historian, translator, and compiler of the first calendars in the Grand Duchy of Lithuania and to draw attention to the relevance of further research, (3) to introduce the extant posthumous account of Pašakauskis’s life written in the tradition and according to the regulations of the Society of Jesus (necrologium, compendium vitae). This is one of the central sources on the life of the Jesuit who contributed substantially to Lithuanian and Polish culture. The Latin original and the annotated Lithuanian translation of this biographical text on Pašakauskis constitute a separate publication. The text of the obituary used for the publication is kept in the Archivum Romanum Societatis Iesu (Rome), while the copy of the obituary attached to the text of Pašakauskis’s largest manuscript work, ‘De viris illustribus Provinciae Lithuaniae’, comes from the Jesuit archive in Cracow (Archiwum Prowincji Południowej Towarzystwa Jezusowego w Krakowie).